1984
DOI: 10.1007/bf00048385
|View full text |Cite
|
Sign up to set email alerts
|

Somatic cell fusion as a source of genetic rearrangement leading to metastatic variants

Abstract: Tumor cell populations displaying metastatic properties often have higher gene dosage than their less malignant progenitor tumors, as shown by increased ploidy levels, chromosome duplication and gene amplification. The acquisition by tumor cells of high chromosome numbers may be due to endoreduplication or somatic hybridization either between tumor cells or between tumor and host cells. All such mechanisms increase genetic variability and instability in tumor cells since they trigger a polyploidization-segrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 185 publications
(257 reference statements)
2
45
0
Order By: Relevance
“…Previous studies have shown that activated stroma is involved in tumorigenesis, and that within malignant lesions, it supports angiogenesis and extracellular matrix remodeling (29,30). We propose that in established tumors, activated stroma may also be genetically transformed, enhancing aggressiveness and metastatic potential because it is composed of hybrid cell variants expressing properties that differ from those of either parental cell (18,31,32). That is, when genetic alterations are induced in stroma by its malignant epithelial partner, the resultant tumor-now a mixture of transformed cell types-will augur a poor prognosis for the patient.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown that activated stroma is involved in tumorigenesis, and that within malignant lesions, it supports angiogenesis and extracellular matrix remodeling (29,30). We propose that in established tumors, activated stroma may also be genetically transformed, enhancing aggressiveness and metastatic potential because it is composed of hybrid cell variants expressing properties that differ from those of either parental cell (18,31,32). That is, when genetic alterations are induced in stroma by its malignant epithelial partner, the resultant tumor-now a mixture of transformed cell types-will augur a poor prognosis for the patient.…”
Section: Discussionmentioning
confidence: 94%
“…10 Moreover, evidence from transformation of mouse epithelial cells also indicates the appearance of tetraploid cells before they undergo a period of chromosome instability. 11 Several processes that cause tetraploidization, including chromosome nondisjunction (which promotes cleavage furrow regression), 12 persistent telomere damage 13 and virus-mediated cell fusion, 14 have been implicated in tumorigenesis. Finally, tetraploids generated by transiently blocking cytokinesis in p53-null mouse mammary epithelial cells can trigger tumor formation after injection into nude mice.…”
Section: Introductionmentioning
confidence: 99%
“…Such non-random changes may occur at an early stage in tumorigenesis and can be characteristic or even unique for specific tumor types (Showe and Croce 1987;Bloomfield et al 1987;Hansen and Cavenee 1987). Non-random changes are also associated with an increased metastatic potential (Larizza and Schirrmacher 1984). Chromosomes can exhibit highly complex structural alterations, especially in some epithelial tumors, and these complex alterations are often associated wittl progressive biologi-cal features of malignancy that are detrimental to the organism.…”
Section: Introductionmentioning
confidence: 99%